Sustainable nutrition and the case of vegetable oils to match present and future dietary needs - Mannucci, Pier Mannuccio; Jolliet, Olivier; Meijaard, Erik; Slavin, Joanne; Rasetti, Mario; Aleta, Alberto; Moreno, Yamir; Agostoni, Carlo (Frontiers in Public Health, 2023)
Sustainable nutrition represents a formidable challenge aiming to provide people with healthy, nutritious and affordable food, while reducing waste and impacts on the environment. Acknowledging the complexity and multi-dimensional nature of the food system, this article addresses the main issues related to sustainability in nutrition, existing scientific data and advances in research and related methodologies. The evolving picture of sustainable nutrition requires interdisciplinary research based on appropriate analyses of big data in populations undergoing emerging behavioral and environmental pressures. We selected vegetable oils as a case study in order to figure out the challenges of sustainable nutrition. Oils represent a major energy source at a global level and their role in sustainable nutrition should be considered beyond pure nutritional facts, at the light of soil preservation, local resources and human needs in terms of health, employment and socio-economic development.